PERAN ORANG TUA DI LINGKUNGAN NUCLEAR FAMILY DAN EXTENDED FAMILY DALAM MENSTIMULASI KEMANDIRIAN ANAK USIA DINI DI DESA BOTO LEMPANGAN KECAMATAN SINJAI BARAT - Nurhayati; A.Sri Mardiyanti Syam3; Hasan (Institut Agama Islam Negeri Bone, 2025)
This thesis discusses the role of parents in the nuclear family and extended family environment in stimulating the independence of early childhood in Boto Lempangan Village, West Sinjai District. The aim of this research is to determine the role of parents in the nuclear family and extended family environment in stimulating the independence of early childhood in Boto Lempangan Village, West Sinjai District. The type of research used is descriptive qualitative with a research approach using a sociological approach and a psychological approach. This research uses data analysis techniques with the process of reducing data, presenting data and drawing conclusions. The results of the research show that the role of parents in stimulating children's independence in the nuclear family environment in Boto Lempangan Village, West Sinjai District is seen when carrying out the role of modeling, mentoring, organizing and teaching in stimulating early childhood independence, while the role of parents in the extended family environment in Boto Village The field of West Sinjai District is only visible when carrying out modeling and teaching roles in stimulating children's independence, while the role of mentoring and organizing is not yet visible. The independent behavior of early childhood in the nuclear family environment in Boto Lempangan Village, West Sinjai District appears to have good emotional independence and behavioral independence, whereas in the extended family environment in Boto Lempangan Village, West Sinjai District, they have not shown good emotional independence and behavioral independence. Keywords: The Role of Parents, Children's Independence